Overlooked biodiversity of mitochondrial lineages in Hemiodus (Ostariophysi, Characiformes) - Nogueira, Acacio F. [UNESP]; Oliveira, Claudio [UNESP]; Langeani, Francisco [UNESP]; Netto-Ferreira, Andre L. (Wiley-Blackwell, 2020)
Hemiodus is the largest genus of the South American freshwater fish family Hemiodontidae, with 23 valid species. However, the species-level diversity of Hemiodus remains uncertain since morphological studies have indicated additional species. Also, the phylogenetic relationships among species and species boundaries within this genus are still unresolved. Herein, we sequenced the barcode (COI) gene of 19 species of Hemiodus on which undertook molecular species delimitation methods (automatic barcode gap discovery [ABGD], generalized mixed Yule coalescent [GMYC] and Poisson tree process [PTP]) and the standard DNA barcoding procedure to establish species boundaries and cast light on putative new species in the genus. We also provide a COI-based phylogenetic hypothesis for Hemiodus by maximum-likelihood (ML) analysis, the first at species level. The results of ABGD, GMYC and PTP indicate that around 30 MOTUs (range: 28-32) exist for Hemiodus within our data set of 19 valid species with concordance among strategies (i.e. equal results) in delimiting 24 MOTUs. Using classical DNA barcoding procedures, we settled on 28 MOTUs for Hemiodus. Undescribed morphospecies (i.e. feasible for description or taxonomic validation), as well as cryptic species (i.e. lineages with high genetic distance but indistinguishable in external morphology), are proposed. Even with the limitations of a single-locus phylogeny, the ML tree recovered many species and species groups as clades, corroborating, thus, their taxonomic separation. Overall, our results highlight the existence of an overlooked diversity of mitochondrial lineages in Hemiodus that can represent cryptic or poorly scrutinized species. Moreover, this study provides a molecular backbone for future studies on the systematics and evolution of Hemiodontidae taxa.
Keywords: DNA barcoding; freshwater fishes; Hemiodontidae; South America